Maritime Cyber Security - Anyanova, Ekaterina (Law, State and Telecommunications Review, 2024)
[Purpose] The threat of cyber-attacks is very acute. The purpose of this paper is to examine the need of the amendment of rules of international law required for the cyber resilient enterprise. [Methodology] This paper proposes a novel approach investigating whether the amendment of rules of international law is required for the cyber resilient enterprise. The methodology of international legal research and analysis of data is applied. [Findings] The analyses in this paper show the impact of the cyber security on the shipping industry. The proposals of documents on cyber security and recommendations for maritime cyber risk management are discussed. [Practical Implications] This study is useful for practitioners to consider and evaluate the cyber security. This study is useful for graduate students as well. [Originality] Although some research is being conducted in this area, maritime cybersecurity has not been deeply investigated. This paper presents a detailed analysis of legal documents and research published in international studies on the law of cyber security for maritime industry highlighting security problems and challenges.